AB0578 Mepolizumab in the Treatment of Eosinophilic Granulomatosis with Polyangitis. (10th June 2014) - Philipson, R.S.; Anderson, J.; Brown, J.C.; Busse, W.W.; Cid, M.; Gleich, G.; Gross, W.; Guillevin, L.; Ortega, H.; Jayne, D.; Pagnoux, C.; Savage, C.; et al.
Abstract : Background: A double-blind, randomised, placebo-controlled, 60-week study of mepolizumab (300 mg every 4 weeks) in eosinophilic granulomatosis with polyangiitis (EGPA) is being sponsored by GlaxoSmithKline in collaboration with the National Institute of Allergy and Infectious Diseases (NIH) in the US. It is critical to ensure definition of the appropriate EPGA diagnostic criteria and study outcomes for this global study. Objectives: To present the study design, criteria for selection of the study population and study endpoints. Methods: EGPA researchers in North America and Europe were consulted on the critical outcomes required to demonstrate clinical benefit in the treatment of EGPA and the appropriate patient population for investigation in a clinical trial. Results: In this study we modified the American College of Rheumatology criteria for the classification of EGPA by addition of further criteria to ensure that recruited subjects have a definite diagnosis of EGPA determined by the presence of key manifestations of this condition, i.e., asthma plus eosinophilia with two of nine further features of EGPA. Eligible subjects are required to have a history of relapsing or refractory disease and will continue on background standard of care therapy including corticosteroids, with or without immunosuppressive therapy. Key outcomes to demonstrate benefit in the treatment of EGPA were identified as duration of remission (accrued and sustained), reduction in risk of relapse and reduction in corticosteroid usage. Based on this, co-primary endpoints are: i) total accrued duration of remission, where remission = BVAS of zero plus prednisolone dose ≤4 mg/day and ii) proportion of subjects who are in remission at both Weeks 36 and 48 of the 52-week study treatment period. Key secondary endpoints are: i) time to first relapse; ii) average daily prednisolone dose during the last 4 weeks of treatment, iii) the proportion of subjects who achieve remission within the first 24 weeks of the study and then stay in remission. Conclusions: This double-blind, randomised study is adopting modified EGPA diagnostic criteria and novel endpoints with the objective of investigating the efficacy and safety of mepolizumab compared to placebo in subjects with relapsing or refractory EGPA, receiving standard of care therapy. Patient recruitment is being initiated in 2014. Disclosure of Interest: R. Philipson Employee of: GlaxoSmithKline., J. Anderson Employee of: GlaxoSmithKline., J. Brown Employee of: GlaxoSmithKline., W. Busse Consultant for: GlaxoSmithKline., M. Cid Grant/research support: Centocor., Consultant for: GlaxoSmithKline, Roche Pharma., Speakers bureau: BMS., G. Gleich Consultant for: GlaxoSmithKline., W. Gross Consultant for: GlaxoSmithKline., L. Guillevin Consultant for: GlaxoSmithKline., Speakers bureau: Roche Pharma., H. Ortega Employee of: GlaxoSmithKline., D. Jayne Grant/research support: Roche/Genetech, Genzyme., Consultant for: Chemcocentryx, GlaxoSmithKline, Rocher/Genentech, Takeda., Speakers bureau: GlaxoSmithKline, Roche/Genentech., C. Pagnoux Consultant for: GlaxoSmithKline., C. Savage Employee of: GlaxoSmithKline., P. Weller Consultant for: GlaxoSmithKline., M. Wechsler Consultant for: GlaxoSmithKline, Merck, Boehringer Ingelheim, Novartis, Cytos, Medimmune, Teva. DOI: 10.1136/annrheumdis-2014-eular.1764